Terrestrial resonant oscillations during the 11 April 2012 Sumatra doublet earthquake - Nayak, Srinivas; Bagiya, Mala S.; Maurya, Satish; Hazarika, Nava Kumar; Kumar, A.S. Sunil; Prasad, D.S.V.V.D.; Ramesh, D.S. (My University, 2021)
The Earth's background free oscillations at ∼3.7 and ∼4.4 mHz resonantly couple with the atmospheric acoustic modes and thus energy cross-talk between the earth-atmosphere system is maximum at these frequencies. The present study proposes resonant coupling between the Earth's surface and atmosphere during the 11 April 2012 Sumatra doublet earthquake and offer a possible explanation to this occurrence. Following both these earthquakes, prolonged ionospheric oscillations centered at frequency of ∼4 mHz were observed in GPS (Global Positioning System) derived total electron content (TEC) towards north-northeast of the epicenters. We scrutinize these oscillations in terms of the manifestations of plausible non-tectonic and tectonic forcing mechanisms surrounding the epicentral region. Non-tectonic forcing such as the geomagnetic field coupling factor and observation geometry played a critical role in determining the amplitude anisotropy of resonant ionospheric signatures. Further, the Rayleigh waves of the first earthquake (Mw 8.6) were already characterized by an excess of energy at ∼4 mHz. We propose this could make the Mw 8.6 earthquake particularly efficient to excite the 4 mHz resonance in the atmosphere. The resonant ionospheric signatures after the second earthquake (Mw 8.2) were observed to be closely associated with the Earth's free oscillations caused by R2 Rayleigh wave train of the Mw 8.6 earthquake event. Together, all the above point to a scenario where the resonant ionospheric signatures during the Sumatra doublet event were indeed related to the seismic source. Therefore, resonant co-seismic ionospheric signatures could provide additional information on the low-frequency features of seismic ruptures.
Keywords: Terrestrial resonant oscillations; Sumatra doublet earthquake